COMPARISON OF INTRAPARTUM AND NEONATAL OUTCOME AMONG GRAND MULTIPARA AND MULTIPARA: Neonatal Outcome Among Grang Multipara and Multipara - Khan, Maj Fatima Sharif; Arif, Sadia; Arif, Ayesha (Pakistan Armed Forces Medical Journal, 2012)
Objective: To compare the frequency of intrapartum and neonatal complications among grand multipara with age matched multipara.Study Design: Case-Control Study.Place and duration of Study: Department of Obstetrics and Gynaecology, Military Hospital, Rawalpindi, from June 2008 to December 2008.Patients and methods: Sixty five grand multipara (Para>5) and 65 multipara (Para 2-4) aged between 20 to 40 years, with singleton pregnancy of up to 40 weeks and presenting in spontaneous labour were selected. Grand multipara (group A) were analysed during labour for Intrapartum complications and neonatal complications. These were then compared with multipara (group B).Results: The mean age of women in group A was 36.40 } 3.320 years and in group B was 32.60 } 4.650 years. The mode of delivery in both groups was not significantly different (p-value >0.05). The rate of postpartum haemorrhage was however significantly higher in grand multipara (13.83% vs. 3.07%, p-value